Nuevo ejemplar de Cuvieronius hyodon (Proboscidea: Gomphotheriidae) del Pleistoceno de Costa Rica - Acuña Mesén, Rafael (1998)
A lower mastodont molar was found in Nacaome river, Nicoya, Guanacaste, Costa Rica. It is a Pleis- . tocene specimen of Cuvieronius hyodon.C. hyodon and Haplomastodon waringi, mountain and savanna mastodonts respectively, have been found in the same place. This evidence and the dental morphology suggest that they were seasonaly simpatric species with different alimentary niches. Probably H. waringi fed on savanna or prairie plants (very ligneous with high silíca concentration, e.g,Cyperaceae) whereas C. hyodon consumed sQfter plants (the enamel is less damaged).